Serologic prevalence of Toxoplasma gondii in Indian women of child bearing age and effects of social and environmental factors. - Sarman Singh; Arshi Munawwar; Sugandhi Rao; Sanjay Mehta; Naba Kumar Hazarika (PLoS Neglected Tropical Diseases, 2014)
Background Seroprevalence and incidence of toxoplasmosis in women of child bearing age has remained a contentious issue in the Indian subcontinent. Different laboratories have used different patient recruitment criteria, methods and variable results, making these data difficult to compare. Aim To map the point-prevalence and incidence of toxoplasmosis in India. Material and methods In this cross-sectional study, a total of 1464 women of fertile age were recruited from 4 regions using similar recruitment plans. This included women from northern (203), southern (512), eastern (250) and western (501) regions of India. All samples were transported to a central laboratory in Delhi and tested using VIDAS technology. Their age, parity, eating habits and other demographic and clinical details were noted. Results Most women were in the 18-25 years age group (48.3%), followed by 26-30 years (28.2%) and 31-35 years (13.66). Few (45) women older than 35 yr. were included. Overall prevalence of anti-Toxoplasma IgG antibodies was seen in 22.40%, with significantly more in married women (25.8%) as compared to single women (4.3%). Prevalence increased steadily with age: 18.1% in the 18-25 yr. age group to 40.5% in women older than 40 yr. The prevalence was high (66%) in those who resided in mud houses. Region-wise, the highest prevalence was observed in South India (37.3%) and the lowest (8.8%) in West Indian women. This difference was highly significant (P<0.001). Prevalence was 21.2% in East India and 19.7% in North India. The IgM positivity rate ranged from 0.4% to 2.9% in four study centers. Conclusions This pan-India study shows a prevalence rate of 22.4% with a wide variation in four geographical regions ranging from as low as 8.8% to as high as 37.3%. The overall IgM positivity rate was 1.43%, indicating that an estimated 56,737-176,882 children per year are born in India with a possible risk of congenital toxoplasmosis.